Comprehensive management of water resources from Governance: Case study in Quebradanegra, a municipality in Colombia - Ramírez Bustos, Eduardo; Medina Vásquez, Misael E. (Cooperativismo & Desarrollo, 2023)
The general objective of the research that gave rise to this article was to identify the processes of comprehensive management of water resources, which from governance are developed in a territory, taking the municipality of Quebradanegra, Cundinamarca, Colombia as a case study. The methodology that guided the research had an inductive nature based on direct observation and interaction, both in rural and urban areas of the territory, based on aspects of the context. Among the most relevant results, we can point out the social and cultural relationships that are woven and developed around 19 identified community aqueducts, which constitute activators of the development of the territory, processes in which elements of water management are evident through collective action by the inhabitants, who in turn become local social actors with the support of municipal, departmental and national government entities. A conclusion from this research is that participation is a mechanism that allows the construction of power from below, that is, it is an indispensable strategic element in the construction of water governance. Consequently, the identification of actors and their equitable participation in the policies developed around the use, control and management of water, with a true distribution of power and recognition of differences, is fundamental for water governance.
Keywords: governance; integrated management; water resource; social actors; collective participation; collective action; water basin; water territory